(NvELEZOBETONNYE KONSTRUKCII (B:s ((N|KSPERIMENTALXNO(B-(NTEORETI^ESKIE ISSLEDOWANIQ(B) : [(NsBORNIK STATEJ(B] /s - (NkAUNASSKIJ POLITEHNI^ESKIJ INSTITUT(B.s (NwILXN@SSKIJ FILIALs ((NwILXN@S (B:s (NmINTIS(B,s, 1967)
(NrEZ@ME STATEJ NA LIT(B. (NQZ(B.s
(NbIBLIOGR(B.: (NW KONCE STATEJs
Keywords: (NvELEZOBETONNYE KONSTRUKCII s -- (NiSSLEDOWANIE s -- (NsBORNIKIs